PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERASI - Kharisma, Putri; Priyadi, Maswar Patuh (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2023)
The research aimed to examine: 1) the effect of profitability on the firm value; 2) the effect of firm size on the firm value; 3) Corporate Social Responsibility which moderated the effect of profitability on the firm value; 4) Corporate Social Responsibility which moderated the effect of the firm size on the firm value. The population was Healthcare companies listed on the Indonesia Stock Exchange (IDX) during 2017-2021. Furthermore, the data collection technique used a purposive sampling technique. From 23 Healthcare companies, there were 18 companies that fulfilled the criteria as the sample. In total, there were 90 data observation samples. Moreover, the data analysis technique used multiple linear analyses with SPSS (Statistical Product and Service Solution) 26 versions. The result indicated that: 1) profitability had a positive effect on the firm value; 2) firm size did not affect the firm value; 3) Corporate Social Responsibility was able to moderate the profitability on the firm value; 4) Corporate Social Responsibility was able to moderate the firm size on the firm value.